Implementation of the Target: Type 2 Diabetes - Heart Failure Initiative - Hillis, Hannah Sherry D. (My University, 2022)
Heart failure is a serious, incurable medical condition affecting millions of adults in America. The risk for heart failure is increased by unhealthy behaviors such as smoking and a diet high in fat, salt, and cholesterol. Excessive alcohol intake and a sedentary lifestyle also increase heart failure risk. Some of the most common risk factors include medical conditions such as coronary artery disease, diabetes, hypertension, obesity, and valvular heart disease. The American Heart Association (AHA) and the American Diabetes Association (ADA) collaborated and developed the Target: Type 2 Diabetes℠ - Heart Failure (HF) initiative. The initiative aims to promote a targeted approach to implementing social change by providing patients and healthcare practitioners the evidence-based tools and resources to decrease morbidity and mortality due to cardiovascular diseases. The purpose of this evidence-based project was to implement the Target: Type 2 Diabetes℠ – HF initiative within the organization and improve compliance with the measures among the physician, nursing, and continuity of care (social workers and case managers). The project aimed to promote increased utilization of evidence-based assessment and medications and ensure appropriate patient education and post-discharge support. This project found that by having a structured quality improvement plan assists to ensure comprehensive implementation of and increased compliance with evidence-based care for diabetes patients hospitalized with heart failure.
Keywords: Heart failure; Diabetes; Evidence-based care; Initiative; Quality improvement